Microwave-Assisted Synthesis of Eggshell-Derived Hydroxyapatite for Antibacterial Toothpaste Enriched with Avocado Seed Powder and Extract - Gabrielle Callista Dwi Putri; Atiek Rostika Noviyanti; Yudha Prawira Budiman; Suryana Suryana; Azman Bin Ma’Amor (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2026)
Hydroxyapatite (HA) is a biomimetic material widely used in toothpaste due to its structural similarity to dental enamel. This study aimed to develop an antibacterial toothpaste using HA synthesized from eggshell waste via a microwave-assisted method and enriched with avocado seed (Persea americana Mill.). HA was prepared at a Ca/P ratio of 1.67 using EDTA as a chelating agent and characterized by XRD, FTIR, and SEM. The results confirmed the formation of HA with residual calcite and nanoscale morphology. The optimal EDTA:Ca ratio (0.5:1) yielded the highest HA fraction (82.5 wt%) and crystallinity (78.23%). All toothpaste formulations met physicochemical standards, with pH ranging from 8.93 to 10.0, foam stability between 72.4% and 94.1%, and spreadability between 3.0 and 4.7 cm. Antibacterial tests against Streptococcus mutans ATCC 25125 revealed that avocado seed powder exhibited strong initial inhibition (37.7 mm) but decreased after 30 days of storage, while the extract provided more stable activity (10.09 mm). These findings indicate the potential of combining HA with avocado seed derivatives as a natural and sustainable antibacterial toothpaste formulation. The finding that avocado seed extract exhibits more stable antibacterial activity than powder is particularly important for pharmaceutical industries and dental biomaterial development, as it highlights the necessity of using extract-based formulations to ensure long-term efficacy and shelf stability.